Pengaruh Penyajian Laporan Keuangan, Aksebilitas Laporan Keuagan dan Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Keuagan Daerah Pemerintah Kabupaten Pulau Morotai - Fauzan Ari Yunus; Abdul Hadi; Sirat Hartaty Hadady (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The Effect of Presentation of Financial Statements, Accountability of Financial Statements and Internal Control on the Accountability of Regional Financial Management of the Morotai Island Regency Government. Head of the supervisory commission Abdul Hadi Sirat and members of the Supervisory Commission Hartaty Hadady. This study aims to analyze the effect of the presentation of financial statements, the accessibility of financial statements and internal control on the accountability of regional financial management. This research is quantitative research. The population in this study were all parts involved in regional financial management in the OPD of Morotai Island Regency.... The sampling technique used popusive sampling. The data collection technique used in this study used a survey method. The data used is primary data in the form of questionnaires distributed to respondents. Based on the results of the study, it shows that partially the presentation of financial reports has no effect on the accountability of regional financial management, the accessibility of financial reports has a significant positive effect on the accountability of regional financial management and internal control has a significant positive effect on the accountability of regional financial management.